Heavy metal biomarker: Fish behavior, cellular alteration, enzymatic reaction and proteomics approaches - Sabullah M.K.; Ahmad S.A.; Shukor M.Y.; Gansau A.J.; Syed M.A.; Sulaiman M.R.; Shamaan N.A. (2024)
Indexed by SCOPUS/WOS